The noise manual - Meinke, Deanna K.; Berger, Elliott H.; Discoll, Dennis P.; Neitzel, Richard L.; Bright, Kathryn (American Industrial Hygiene Association, 2022)
« This leading noise resource is specifically written for those with a technical interest in hazardous noise and for anyone who desires an improved general understanding of the subject. It addresses noise-related issues with the workplace and those arising in the community, with a focus on hearing loss prevention strategies. »--Quatrième de couverture.